PENINGKATAN UNJUK KERJA MOTOR BENSIN DENGAN PENAMBAHAN CAMPURAN LPG-UDARA - Agus Subekti Prakoso; Digdo Listyadi Setyawan; Santoso Mulyadi (STATOR: Jurnal Ilmiah Mahasiswa Teknik Mesin, 2018)
Internal Combustion Engine (ICE), air-fuel ratio (AFR) are important thing. By adding stoichiometric AFR mixture of air-LPG can improve efficiency of engine performance. This study aims to determine the best performance of petrol engine with addition of air-LPG mixture including torque, horse power, fuel consumption and exhaust emission levels with a fixed carburetor setting. The method of this research is to conduct motorcycle performance test without addition of air-LPG mixture and using addition with variation of 10,20 and 30 ml/min of LPG debit at full throttle for dyno test, idle for exhaust gas analyze and constant rpm every 1000 rpm from 1000 to 9000 rpm for fuel consumption test. The result show LPG 20 ml/min is good at dyno test, LPG 30 ml/min is good at fuel consumption and exhaust gas analyze. This shows that the addition of LPG 20 ml/min is the peak of torque and horse power increase due to the poor volumetric efficiency initiated on 30 ml/min, But LPG 30 ml/min is good at fuel consumption and gas analyze due to the decrease of the vacuum of intake manifold and good homogeneity. Keyword: Air-LPG mixture, internal combustion engine, performance.